2022
DOI: 10.3390/en15020626
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics of Premixed Hydrogen/Air in an Undulate Microchannel

Abstract: This work reports a numerical investigation of microcombustion in an undulate microchannel, using premixed hydrogen and air to understand the effect of the burner design on the flame in order to obtain stability of the flame. The simulations were performed for a fixed equivalence ratio and a hyperbolic temperature profile imposed at the microchannel walls in order to mimic the heat external losses occurred in experimental setups. Due to the complexity of the flow dynamics combined with the combustion behavior,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…PFB, though initially observed without distinction from FREI, was first identified in the course of micropropulsion studies conducted with wavy geometries [81,82], involving various inlet velocities and equivalence ratios, using a mixture of H 2 and air. The geometry used is similar to our research, and it incorporated different wall conditions (hyperbolic and linear temperature profiles, as well as adiabatic conditions).…”
Section: Pfb: Pulsatory Flame Burstmentioning
confidence: 99%
See 1 more Smart Citation
“…PFB, though initially observed without distinction from FREI, was first identified in the course of micropropulsion studies conducted with wavy geometries [81,82], involving various inlet velocities and equivalence ratios, using a mixture of H 2 and air. The geometry used is similar to our research, and it incorporated different wall conditions (hyperbolic and linear temperature profiles, as well as adiabatic conditions).…”
Section: Pfb: Pulsatory Flame Burstmentioning
confidence: 99%
“…In a recent study by Resende et al [82], flame dynamics within a wave-shaped combustor featuring substantial divergence and convergence variations were investigated. The study employed a hydrogen/air mixture and revealed a pronounced interaction between fluid dynamics and chemical reactions.…”
Section: Investigations In Wavy Wall Geometriesmentioning
confidence: 99%
“…al. [19], reported the influence of flame and flame stability by the design of the burner through a numerical simulation for the combustion of premixed hydrogen/air in an undulate microchannel. As flow dynamics and combustion behavior are so complicated, only the effect of the fuel inlet rate on the flame characteristics have been taken into account, keeping other variables the same.…”
Section: Introductionmentioning
confidence: 99%